Habitat‐associated skew of clone abundance in the Pseudomonas aeruginosa population. Issue 6 (December 2015) - Wiehlmann, Lutz; Cramer, Nina; Tümmler, Burkhard
Summary: The population structure of the cosmopolitan P seudomonas aeruginosa was investigated by genotyping 2921 isolates from 1448 independent habitats with a custom‐made 58 binary marker microarray. Of 323 identified clone types, 109 clones made up 82% of the population. The 20 most frequent clones had an absolute share of 44% indicating that the P . aeruginosa population is dominated by few epidemic clonal complexes. The frequency distribution of common clones was different between inanimate habitats and human niches. The three most abundant clones in the environment were rare among isolates from human infection. Conversely, disease‐associated isolates either belonged to ubiquitous clones such as C and PA14 or to clones that were uncommon in the environment. The P . aeruginosa population consists of major clones that are just as versatile in their habitat and geographic origin as the whole species and of minor clones with preference for a peculiar niche.